Removal of Cu(II) Ions from Aqueous Solutions by the Activated Carbon Obtained from Pine Cone - Gecgel, Unal; Sezer, Kenan; Kolancilar, Hakan (Asian Journal of Chemistry, 2010)
The activated carbon obtained from pine cone was investigated as a new adsorbent to remove copper(II) ion from aqueous solution. The adsorption process of copper(II) ion was carried out in a batch mode and the effects of adsorbent concentration (0.25-1.00 g/100 mL), initial pH's (2.0-6.0) and initial metal ion concentrations (25-100 mg/L) were investigated. Maximum removal capacity of the copper(II) ion from aqueous solutions was achieved at pH 5.0. Adsorption data was well fitted to the Langmuir and Freundlich isotherms. Langmuir monolayer capacity was a value of 15.05 mg/g. The results in this study indicate that the activated carbon obtained from pine cone can be an effective adsorbent for removal of copper(II) ions from aqueous solution.